Detection of Gene Localization in a Large Concomitant Strabismus Family - Kadriye Erkan Turan; Emin Cumhur Şener; Ali Şefik Sanaç (Türk Oftalmoloji Dergisi)
Purpose: To define the gene locus related with concomitant strabismus in a large exotropia family. Material and Method: A three-generation family including 31 individuals among which 17 members had basic exotropia and 3 members had intermittent exotropia with known genome-wide analysis was investigated. The data of genome-wide analysis was evaluated under the assumed pattern of autosomal dominant inheritance with incomplete penetrance which was supported by pedigree analysis. Detailed haplotype analysis of four regions on 3 chromosomes (chromosome 7, 13 and 18) which had positive lod scores in previous studies was performed. Results: The first region on chromosome 13 was excluded regarding haplotype analysis, but the second region could not be excluded because of the high homozigocity in the family. The region which had 200.000 bases on chromosome 18 could not be excluded as well. The region which had 9 Mb on 7p14.1 was common for all family members. 7p14.1 locus is considered as the most likely region responsible for the inheritance of strabismus in regard with familial inheritance and crossing-over pattern. Discussion: The 7p14.1 locus identified in this study is a novel site and it is different from the regions on chromosome 7 which were reported in previous studies. To the best of our knowledge, this is the first study demonstrating the presence of critical recombinations across three generations and will shed light for further studies which will define the specific gene. (Turk J Ophthalmol 2013; 43: 407-12)